An Energy Efficient Mac Layer Design for Wireless Sensor Network - Ghazvini, Mohammad Hossein Fotouhi (2008)
Recent technological advances in sensors, low power integrated circuits, and wireless communications have enabled the design of low-cost, lightweight, and intelligent wireless sensor nodes. The IEEE 802.15.4 standard is a specific Wireless Personal Area Network (WPAN) standard designed for various wireless sensor applications. Idle listening, packet collision, control packet overhead and overhearing are considered as energy consuming resources in WSNs. As the idle listening and packet collision are two major power consuming parts, we considered two solutions for reducing both of them to achieve an energy efficient protocol. We concentrate on the MAC layer design to overcome the energy consumption by radio management procedure and the backoff exponent mechanism. In the radio management, we analyze the contention part of the active duration of the MAC IEEE 802.15.4 standard superframe and allow nodes to enter the sleep state regarding to their available data for transmission instead of staying awake for the entire active period. This method will be useful especially when sensors do not have any data to send. The proposed non-persistent Carrier Sense Multiple Access (np-CSMA) protocol employs backoff exponent management mechanism. This algorithm helps the network to be reliable under traffic changes and saves more energy by avoiding collision. It assigns different range of BE (backoff exponent) to each node with respect to node’s contribution in network traffic. In our scheme a coordinator can observe the network traffic due to the data information associated with devices. It can manage the Personal Area Networks (PANs) devices by the beacon packet to go to sleep mode when they do not have any packet to send. In this thesis, by using the sleep period together with backoff exponent management in our protocol design, the amount of energy consumption will be reduced. The proposed model has been compared to original 802.15.4 standard and the existing Adaptive Backoff Exponent (ABE) MAC protocol to illustrate the improvement. Moreover, the BE management algorithm derives better system performance such as end-to-end delay, throughput, packet delivery ratio and Link Quality Indicator (LQI). The proposed model has been designed in such a way that the introduction of extra sleep period inserted in superframe improves the energy efficiency while maintaining other system performance parameters. The proposed MAC protocol has improved the energy consumption around 60% as compared to ABE-MAC. The proposed MAC protocol with an extra radio management technique together with backoff management procedure can achieve 70% more energy saving than MAC IEEE 802.15.4 standard.